Analiza możliwości kompleksowego zagospodarowania zasobów złoża węgla brunatnego Gubin, kopalin towarzyszących oraz odpadowych surowców mineralnych = Analyze of complex utilization of lignite deposit resources, accompanying minerals and waste raw materials - Naworyta, Wojciech (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Possibility of utilization of accompanying minerals of Gubin lignite deposit has been analyzed. The practice in Polish lignite mines and experiences in that field has been presented as the background. The necessity of utilization of waste raw materials from lignite power plant was discussed. The problems of water utilization from dewatering system were shown.
Keywords: węgiel brunatny; kopaliny towarzyszące; gips syntetyczny; racjonalnagospodarka zasobami; lignite; accompanying minerals; synthetic gypsum; rational utilization ofresources